Silver oxide nano-colloid based selective colorimetric sensor for the recognition of cystine in aqueous solution. (6th June 2020) - Andal, V.; Bhuvaneswari, G.
ABSTRACT: Sodium alginate modified Ag2 O (SA@Ag2 O) nano-colloid is synthesised and studied colorimetric response towards eight selected amino acids in aqueous medium at room temperature. The synthesised SA@Ag2 O nano-colloid showed a surface plasmon band at 469 nm. Distinctive colour change of the dark brown colloid to colourless is observed in the case of Cystine. Among the eight amino acids studied such as D-L- Aspartic acid, L-Glutamic acid, Glycine, Alanine, D-L Methionine, L-Cysteine, L-Cystine and L-Tyrosine. L-Cystine stands out by completely decolorising the brown colloid which can be detected by the 'naked-eye'. This sensor selectively detects Cystine. To understand the sensing mechanism, the amino acid treated SA@Ag2 O colloids were characterised by UV, XRD, FTIR and TEM analysis. This approach offers several advantages such as simplicity, low cost and high sensitivity. Graphical abstract: An environment friendly approach for the detection of cystine in aqueous solution using SA@Ag2 O nano-colloid